Intraosseous carcinoma of the jaws: A clinicopathologic review. Part III: Primary intraosseous squamous cell carcinoma. Issue 6 (31st January 2012) - Woolgar, Julia A.; Triantafyllou, Asterios; Ferlito, Alfio; Devaney, Kenneth O.; Lewis, James S.; Rinaldo, Alessandra; Slootweg, Pieter J.; Barnes, Leon; W. Eisele, David
Abstract This is the third part of a review of the clinicopathologic features of intraosseous carcinoma of the jaws (IOCJ). In parts 1 and 2, we discussed metastatic and salivary‐type and odontogenic carcinomas, respectively. This part deals with primary intraosseous squamous cell carcinoma. Again, based on a critical approach, we emphasize histopathologic features, diagnostic difficulties, discuss histogenesis, and highlight areas of uncertainty. The 3‐part review also offers speculations on how future studies may refine our understanding of the unusual and interesting IOCJ. © 2012 Wiley Periodicals, Inc. Head Neck, 2012